Cancer pain self‐management in the context of a national opioid epidemic: Experiences of patients with advanced cancer using opioids. Issue 17 (27th April 2021) - Azizoddin, Desiree R.; Knoerl, Robert; Adam, Rosalind; Kessler, Daniela; Tulsky, James A.; Edwards, Robert R.; Enzinger, Andrea C.
Abstract : BACKGROUND: The US opioid epidemic has prompted dramatic changes in public attitudes and regulations governing opioid prescribing. Little is known about the experiences of patients with advanced cancer using opioids in the context of the epidemic. METHODS: Semistructured interviews of 26 patients with advanced cancer were conducted between May 2019 and April 2020; their experiences self‐managing chronic pain with opioids were evaluated. RESULTS: Patients consistently described the negative impact of the opioid epidemic on their ability to self‐manage pain. Negative media coverage and personal experiences with the epidemic promoted stigma, fear, and guilt surrounding opioid use. As a result, many patients delayed initiating opioids and often viewed their decision to take opioids as a moral failure—as "caving in." Patients frequently managed this internal conflict through opioid‐restricting behaviors (eg, skipping or taking lower doses). Stigma also impeded patient‐clinician communication; patients often avoided discussing opioids or purposely conveyed underusing them to avoid being labeled a "pill seeker." Patients experienced structural barriers to obtaining opioids such as prior authorizations, delays in refills, or being questioned by pharmacists about their opioid use. Barriers were stressful, amplified stigma, interfered with pain control, and reinforced ambivalence about opioids. CONCLUSIONS: The US opioid epidemic has stigmatized opioid use and undermined pain management in individuals with advanced cancer. Interventions seeking to alleviate cancer pain should attend to the multiple, negative influences of the opioid crisis on patients' ability to self‐manage. LAY SUMMARY: Patients with advanced cancer suffer from significant pain and frequently receive opioids to manage their pain. Of the 26 patients with advanced cancer interviewed, the majority of patients experienced stigma about their opioid use for cancer pain management. All patients felt that the opioid epidemic fostered this stigma. Several struggled to use opioids for pain because of this stigma and the logistical complications they experienced with pharmacies and insurance coverage. Many were afraid to share their concerns about opioids with their providers. ​ Abstract : This qualitative analysis found that the US opioid epidemic has stigmatized opioid use and undermined pain management in individuals with advanced cancer. Patients reported significant guilt and fear around using opioids and endorsed restricting or avoiding opioids when managing their advanced cancer pain.